Broadband ventilated acoustic metamaterial design with coupled space-coiled resonators - Karakoyun, Ahmet. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
In this thesis, broadband ventilated acoustic metamaterial design with coupled space-coiled resonators is studied. The main aim is to determine acoustic metamaterial designs, which provide high level of sound attenuation in a wide frequency range and results in minimum air pressure loss during airflow. The number and dimensions of the resonators are optimized for this aim. In order to accomplish coupling with more than two resonators, i.e., channels, an analytical model of the design having one resonator is obtained by using the transfer matrix method. Consequently, transmission loss characteristics are compared with the finite element model for verification. After verification for one resonator, the analytical model of the design having two resonators is obtained by using parallel connection of transfer matrices. Once the derivation regarding parallel connection of transfer matrices is done, a new methodology for the analytical model of the design having more than two resonators is proposed. By using this methodology, optimization is conducted by changing the number and/or the dimensions of the coupled resonators to accomplish sound isolation in the widest frequency range for a given transmission loss constraint. After determining the proper number and dimensions of the resonators, the finite element model of the proposed design is constructed. By using genetic algorithm, the analytical resonator lengths are updated to determine the lengths in the finite element model. Parametric studies are conducted to show the dependence of isolation bandwidth on target transmission loss and channel dimensions. It is shown that for low transmission loss targets such as 10 dB, a two channel design can provide both large isolation bandwidth and low pressure loss. On the other hand, for high transmission loss targets such as 50 dB or 60 dB, a three or four channel design can provide both wider isolation bandwidth and lower pressure loss than a two channel design.
Keywords: Resonators -- Design.; Acoustic metamaterial.